2016
DOI: 10.1136/gutjnl-2015-310838
|View full text |Cite
|
Sign up to set email alerts
|

ZEB1-induced tumourigenesis requires senescence inhibition via activation of DKK1/mutant p53/Mdm2/CtBP and repression of macroH2A1

Abstract: The tumourigenic capacity of ZEB1 depends on its inhibition of cancer cell senescence through the activation of a herein identified new molecular pathway. These results set ZEB1 as a potential target in therapeutic strategies aimed at inducing senescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 59 publications
2
34
0
Order By: Relevance
“…A previous study demonstrated that ZEB1 expression enhanced the aggressive tumour cell phenotype by remodelling lung cancer extracellular matrix . ZEB1 expression also promoted tumour initiation and progression, which resulted from inhibiting the senescence of colorectal cancer cells . The current study demonstrated that ZEB1 was significantly correlated with Gleason score, TNM and metastasis, in a manner similar to VM.…”
Section: Discussionsupporting
confidence: 68%
“…A previous study demonstrated that ZEB1 expression enhanced the aggressive tumour cell phenotype by remodelling lung cancer extracellular matrix . ZEB1 expression also promoted tumour initiation and progression, which resulted from inhibiting the senescence of colorectal cancer cells . The current study demonstrated that ZEB1 was significantly correlated with Gleason score, TNM and metastasis, in a manner similar to VM.…”
Section: Discussionsupporting
confidence: 68%
“…The development of detection techniques for cSCCs has enabled the timely treatment of this disease, resulting in an increase in the survival rate of patients with cSCCs [23]. Recently, the dysregulation of CtBP expression has been considered a key step in the formation of various human tumors [24][25][26]. K/o of CtBP can increase the induction of apoptosis and inhibit tumorigenesis in vivo [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of H2AFY induces tumorigenicity and expression of the transcription factor ZEB1, which leads to a poor prognosis in patients with colon cancer (24). However, in some studies, H2AFY has been shown to be carcinogenic.…”
Section: Introductionmentioning
confidence: 99%